MRI-Based Radiomics of Basal Nuclei in Differentiating Idiopathic Parkinson’s Disease From Parkinsonian Variants of Multiple System Atrophy: A Susceptibility-Weighted Imaging Study - Pang, Huize; Yu, Ziyang; Li, Renyuan; Yang, Huaguang; Fan, Guoguang (Frontiers in Aging Neuroscience, 2020)
Objectives: To investigate the value of MRI-based radiomic model based on the radiomic features of different basal nuclei in differentiating idiopathic Parkinson's disease (IPD) from Parkinsonian variants of multiple system atrophy (MSA-P). Methods:Radiomics was applied to the 3T susceptibility-weighted imaging (SWI) from 102 MSA-P patients and 83 IPD patients (allocated to a training and a testing cohort, 7:3 ratio). The substantia nigra (SN), caudate nucleus (CN), putamen (PUT), globus pallidus (GP), red nucleus (RN) and subthalamic nucleus (STN) were manually segmented, and 396 features were extracted. After feature selection, support vector machine (SVM) was generated, and its predictive performance was calculated in both the training and testing cohorts using the area under receiver operating characteristic curve (AUC). Results: Nine radiomic features were selected from the PUT, by which the SVM classifier achieved the best diagnostic performance with an AUC of 0.934 in the training cohort and an AUC of 0.866 in the testing cohort. Furthermore, the combined model, which incorporating part III of the Parkinson’s Disease Rating Scale (UPDRSIII)scores into radiomic features of the PUT, further improved the diagnostic performance. However, radiomic features extracted from RN, SN, GP, CN, and STN had moderate to poor diagnostic performance, with AUC values that ranged from 0.744 to 0.878 in the training cohort and 0.532 to 0.731 in the testing cohort. Conclusion: Radiomic features derived from the PUT had optimal value in differentiating IPD from MSA-P. A combined radiomic model, which contained radiomic features of the PUT and UPDRSIII scores, further improved performance and may represent a promising tool for distinguishing between IPD and MSA-P.